Products and Applications of Biopolymers - Johannes Reinhard Verbeek, Casparus; Johannes Reinhard Verbeek, Casparus (IntechOpen, 2012)
It is interesting to consider that biopolymers are by no means new to this world. It is only because of our fascination with petrochemical products that these wonderful materials have been neglected for so long. Today we face a different challenge. Environmental pressure is pushing away from synthetic or petro-chemically derived products, while economic factors are pulling back from often more expensive "green" options. This book presents two aspects of biopolymers; potential products and some applications of biopolymers covering the current relevance of biopolymers.
English
Keywords: Spectrum analysis, spectrochemistry, mass spectrometry; Polymer chemistry